Psychometric Properties of the College Student Subjective Well-Being Questionnaire among Students of the Faculty of Da’wah and Communication at UIN Alauddin Makassar: Uji Validitas dan Reliabilitas Instrumen Kesejahtraan Subjektif pada Mahasiswa Fakultas Dakwah dan Komunikasi UIN Alauddin Makassar - Kurniati, Yessy; Khalil Fahmi, Muhammad; Dirham, Nurazizan; Fitriani, Nabila; Indriyani, Putri (Infomasi dan Promosi Kesehatan, 2026)
Introduction Students’ subjective well-being is an important indicator of mental health and academic functioning in higher education. Measuring subjective well-being requires valid and reliable instruments to ensure that the results obtained are accurate and trustworthy. This study aims to examine the validity and reliability of the College Student Subjective Well-Being Questionnaire (CSSWQ) among students of the Faculty of Da’wah and Communication at UIN Alauddin Makassar. Methods This study employed a quantitative approach with a descriptive design. The research population consisted of all active students of the Faculty of Da’wah and Communication at UIN Alauddin Makassar. The sample included 36 respondents selected using a purposive sampling technique. Data were collected through an online survey. Data analysis included validity testing using item–total correlation and reliability testing using Cronbach’s Alpha coefficient with the assistance of SPSS software. Results The results showed that all 16 items of the CSSWQ instrument were valid, as each item had a calculated correlation coefficient (r-value) greater than the critical r-value (0.3202). The reliability test yielded a Cronbach’s Alpha value of 0.854, indicating high reliability. These findings demonstrate that the CSSWQ instrument has good internal consistency. Conclusion The CSSWQ instrument is proven to be valid and reliable for measuring the subjective well-being of students at the Faculty of Da’wah and Communication, UIN Alauddin Makassar. This instrument can be used as an accurate measurement tool to support the monitoring of students’ psychosocial conditions and as a basis for planning mental health promotion programs in higher education settings.